Potentiality of Using Spreading Sargassum Species from Indonesia as an Interesting Source of Antibacterial and Radical Scavenging Compounds: A Preliminary Study - Ita Widowati; Maya Puspita; Valerie Stiger-Pouvreau; Nathalie Bourgougnon (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2014)
As an archipelagic country with 95,181 km long coastline, Indonesia has great potential as the producer of seaweeds. The diverse phyla of marine macroalgae (red, brown and green seaweeds) are known to produce molecules which are attractive for diverse industries. Applications of algal products range from simple biomass production for food, feed and fuels to valuable products such as sugar polymers, cosmetics, pharmaceuticals, pigments, and food supplements. Seaweeds also have the potential to be used as a source of new bioactive for human, animal or plant health, as well as a source of new synthons and biocatalysts in sustainable chemistry (Bourgougnon and Stiger-Pouvreau, 2011). In this paper, among species of economic value we focus on brown seaweeds belonging to family Sargassaceae and genus Sargassum spreading along Indonesian coasts. Members of this genus are especially abundant in tropical and subtropical regions (Zemke-White and Ohno, 1999). The purpose of this study is to analyze the antibacterial and antioxidant activity of three species of Sargassum, i.e. S. echinocarpum, S. duplicatum and S. polycystum. Both polar and non-polar extracts have been prepared from those three species. In vitro antibacterial activities of extracts were evaluated against Gram-positive bacteria Staphylococcus aureus and Gram-negative bacteria Escherichia coli. Results indicated all the three species tested showed an antibacterial activity. The most effective antibacterial activity against S. aerous was from S. echinocarpum with ethil asetat, inhibition zone 1.13 ± 0.25 mm; S. duplicatum with N-Hexane was most effective against E. coli, 1.20 ± 0.28 mm. Key words: Antibacterial, Sargassum, Staphylococcus aureus, Escherichia coli.